ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP PADA MATERI SEGIEMPAT DAN SEGITIGA - Tresno Sri Wahyuni; Risma Amelia; Rippi Maya (Jurnal Kajian Pembelajaran Matematika, 2019)
This research is motivated by the low mathematical communication skills of junior high school students in mathematics, especially in junior high schools in West Bandung Regency. Students experience learning difficulties in quadrilateral and triangle material. This study aims to determine the level of mathematical communication skills of students. The sample taken was as many as 31 students in class VIII D in one of the junior high schools in Padalarang Subdistrict, West Bandung Regency. The method of this research is qualitative descriptive which is analyzed from the given instrument. The instruments in this study took the form of 5 written test questions. The results of this study indicate that students' ability to complete mathematical communication skills is still lacking. This can be seen from the results of the recapitulation of the overall answers of students who answered correctly as much as 21%, answered incorrectly as much as 76%, and did not answer as much as 3%. Besides that, it can be seen from the results of the score conversion of students that the mathematical communication skills of students are in the very low category, namely students who score less than 55 by 65%.